ANDALIMAN: HARMONIZATION OF SPICES WITH BATAK CULTURE - Puji Hariati; Purwarno Purwarno (University of Kuningan, 2025)
This research aims to describe the relationship among ecolinguistics, andaliman, and Batak Culture. It explains how andaliman as Batak’s spices can hold ecolinguistics and Batak Culture. This study employs a qualitative research approach where the data is taken from observation, interviews, and documentation. The finding indicates that in Batak culture, andaliman is not just a culinary ingredient but also an important part of traditional rituals and festivities. The spice is deeply ingrained in the cultural identity of the Batak people such as: Social Interaction, Batak’s Connection to Nature, Respect for Natural Resources, Spiritual Beliefs, Modern Batak Culture, Preserving Tradition in a Modern World, Andaliman in Tourism, and Cultural Connector. It means that andaliman and and Batak culture is not only ecological but also linguistic and symbolic. Andaliman holds cultural significance to be tied to local stories, practices, and beliefs about the plant's power. The symbolic value of andaliman in these contexts goes beyond its flavor and is woven into the cultural fabric of Batak life. Language functions as a vehicle for passing down traditional ecological knowledge, ensuring the continued use and conservation of plants like andaliman. plays a significant role in shaping attitudes toward the sustainable harvesting of plants like andaliman. The way elders talk about andaliman could serve as a cultural guide to ensuring that its use is sustainable and harmonious with nature.